Impact of supervised physiotherapeutic pelvic floor exercises for treating female stress urinary incontinence - Zanetti, Míriam Raquel Diniz; Castro, Rodrigo de Aquino; Rotta, Adriana Lyvio; Santos, Patrícia Diniz dos; Sartori, Marair; Girão, Manoel João Batista Castello (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Urinary incontinence is a public health problem that affects more than 200 million people worldwide. Stress incontinence is the most prevalent type. Pelvic fl oor muscle exercises have been used for treating it, although there is no consensus regarding their application. The aim of this study was to compare the results from treating female stress urinary incontinence with pelvic fl oor muscle exercises with or without physiotherapist supervision. DESIGN AND SETTING: This was a randomized, prospective, controlled trial in the Urogynecology and Vaginal Surgery Sector, Universidade Federal de São Paulo. METHODS: Forty-four women were randomized to be treated for stress urinary incontinence with pelvic fl oor exercises for three consecutive months, into two groups: one with and the other without physiotherapist supervision. They were evaluated before and after treatment using a quality-of-life questionnaire, pad test, micturition diary and subjective evaluation. Descriptive analysis was used to evaluate the population. The homogeneity of the two groups was evaluated using the Kruskal-Wallis and Chi-squared tests. The success of the two groups after treatment was evaluated using the Wilcoxon test. RESULTS: The supervised group showed statistically greater improvement in the pad test, micturition diary and quality of life than did the control group. In the subjective evaluation, only 23.8% of the control group patients were satisfi ed with their treatment. In the supervised group, 66.8% of patients did not want any other treatment. CONCLUSION: Supervised pelvic fl oor muscle exercises presented better results in objective and subjective evaluations than did unsupervised exercises.